Pelatihan Soal Matematika Tipe PISA bagi Siswa SMK Usia 15 Tahun - Indrie Noor Aini; Kiki Nia Sania Effendi (Jurnal Pengabdian Pada Masyarakat, 2021)
PISA TYPE MATH PROBLEM TRAINING FOR 15-YEAR-OLD VOCATIONAL HIGH SCHOOL STUDENTS. Mathematics is a universal science that underlies the development of modern technology and has an important role in various disciplines and the development of human thinking. PISA (Program for International Student Assessment) is an international study in the context of assessing learning outcomes, one of which aims to test the mathematical literacy of students aged 15 Mathematical literacy is needed not only for mastery of my material. but also requires the use of reasoning, concepts. Mathematical facts and tools in solving everyday problems Given the importance of mathematical literacy skills, this training is a form of community service, especially for students aged 15 years. The method used is the approach method and the method of implementation. The output target of this activity is to provide mastery skills of 15 year old vocational school students of SMK in order to increase their knowledge and skills in Mathematics. The result of this training is the addition of new knowledge for students in math problems. close to their lives. Most students understand the material on the training being carried out, they even look enthusiastic because according to them the tutor who delivers the material is very good at the material presented.